Real-Time Monitoring of Cropping Pattern Using Geospatial Analysis - Gumma, Murali K. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
This contribution will significantly impact agricultural monitoring and decision-making processes through the integration of remote sensing and machine learning. These advancements will lead to more accurate and timely data on crop patterns, enabling better resource management and policy-making.